Experimental Study on Chromaticity Control in Visible Light Communication Systems - Xizheng Ke; Xingxing Wang; Huanhuan Qin; Jingyuan Liang (Photonics, 2023)
To apply visible light communication systems in different scenarios, this article utilizes an excellent temperature-adjustable light source mixed with RGB LEDs and applies it in a visible light communication system. It uses color division multiplexing technology to achieve three-channel communication, thereby improving the communication bandwidth of the system. The communication system adopts three constant current driving circuits to control the duty cycle of Pulse Width Modulation (PWM) of each channel, thereby changing the proportion of RGB LEDs, and obtaining different color temperatures to achieve the purpose of color control for mixed-color LEDs. The experimental results show that when adjusting the color temperature, the change in luminous flux is very small, with fluctuations of less than 2.24%. When adjusting the brightness, the color temperature fluctuation is within 40 K, which is less than the 50 K color temperature limit that the human eye can distinguish, and the average color temperature error is 0.609%. Color tolerance less than 5.5 × 10−3 indicates good dimming effect, and the communication performance of the system is better in the high color temperature range, which is significantly superior to the low color temperature range. When the error rate is below 3.8 × 10−3, the total modulation bandwidth of the three channels reaches 11.7 MHz.